While gender quotas for top positions in the private sector differ across EU countries, they are effective overall - Anja Kirsch; Virginia Sondergeld; Katharina Wrohlich (DIW Weekly Report, 2022)
This second report in the DIW Berlin Women Executives Barometer 2022 explores the designs and effects of gender quotas across Europe, coming to the conclusion that they are an effective instrument for increasing the share of women in top positions at large companies. Furthermore, the quotas differ greatly between the countries, for example in regard to the number of companies subject to the quota, the concrete quota targets, or sanctions. Using European data for the years 2003 to 2021, this report shows that the group of nine EU countries that have introduced a gender quota has a significantly greater share of women on top decision-making bodies than the group of the non-quota EU countries (almost 35 percent compared to 22 percent). Generally, the share of female non-executive directors (in Germany, this refers to supervisory board members) is higher than the share of female executive directors. The effectiveness of quota regulations has been confirmed by calculations that take into account that certain factors differ by country, such as cultural norms regarding gender roles or labor market policy and family policy. Against this background, the President of the European Commission's initiative to advance a draft directive for more equal representation of men and women on the boards of large companies appears helpful. The proposal is currently being blocked in the Council of the EU. If this changes, the share of women on boards could increase, especially in the countries that do not yet have a mandatory gender quota.
Keywords: D22; J16; J59; J78; L21; L32; M14; M51; 330; corporate boards; board composition; boards of directors; board diversity; Europe; women directors; gender equality; gender quota; Germany; management; private companies; public companies; supervisory boards; executiveboards; CEOs; women; finance industry; financial sector; private and public banks; insurance companies